2020
DOI: 10.1108/jieb-04-2020-0026
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and achievements in student learning experiences in a business school’s at-home internationalization programs in China

Abstract: Purpose The purpose of this ontologically qualitative research study was to (a) explore student narratives regarding their educational experiences in at-home internationalization programs; (b) provide an in-depth narrative analysis of student learning challenges and achievements; and (c) add valuable research-based knowledge of student-described experiences for use by program administrators. Design/methodology/approach Participants were selected with a form of four-stage non-proportional stratified sampling.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 76 publications
(98 reference statements)
1
2
0
Order By: Relevance
“…Most students are found anxious due to the long working hours; consequently, they cannot find sufficient time to complete the assigned tasks on time. The same factor has been reported by Langtree et al ( 2018 ), where academic workload contributes significantly to generating stress among students and is a major challenge for undergraduate business students in Chinese universities (Tang et al 2020 ). Therefore, it is suggested that concerned educational authorities set policies that do not exceed students’ academic load and they should be given adequate time to complete tasks.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Most students are found anxious due to the long working hours; consequently, they cannot find sufficient time to complete the assigned tasks on time. The same factor has been reported by Langtree et al ( 2018 ), where academic workload contributes significantly to generating stress among students and is a major challenge for undergraduate business students in Chinese universities (Tang et al 2020 ). Therefore, it is suggested that concerned educational authorities set policies that do not exceed students’ academic load and they should be given adequate time to complete tasks.…”
Section: Discussionsupporting
confidence: 70%
“…As a result of their positive attitudes and behaviors, students can easily achieve their learning objectives (Luthans et al 2012 ). Unfortunately, many studies report that academic pressure might negatively influence some students’ mental health and cause stress and depression in the university environment (Rehmani et al 2018 ; Tang et al 2020 ). Such depressed conditions among students often adversely affect their academic achievement and satisfaction (Mirhosseini et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, in Tang et al's (2021) study, students learned to see the connection between the challenges they had encountered and their effort and successes. This also refers to the concept of learned optimism (Seligman, 1991), that students learn to believe that they can conquer challenges and achieve what they want to achieve.…”
Section: Theoretical Backgroundmentioning
confidence: 99%